Practitioner (mis)understandings of coercive control in England and Wales - Robinson, Amanda Lea (Criminology & criminal justice, 2018)
Coercive control is harmful behaviour recently criminalized in England and Wales. The extent to which the work of practitioners is informed by an understanding of coercive control therefore requires investigation. Using data from two mixed methods multi-site studies, this article suggests that practitioners’ recognition of coercive control does not seem to be universally poor or skilled, but rather depends on the characteristics of the situation itself, the organizational context in which practitioners work and the stage at which they are evaluating whether coercive control is present. The absence of a clear understanding of the importance of coercive control when making judgements about victims and perpetrators has serious implications for the efficacy of current approaches to domestic abuse. Purposeful and systematic efforts to support practitioners to recognize and respond effectively to coercive control are required.